Open Access to Information Sources, Sustainable Scientific Development - Radu, Alexandra (Annals of Spiru Haret University. Economic Series, 2025)
This paper aims to treat the sensitive subject of open access to academic information sources, from the perspective of the concept of sustainable development. In this sense, the paper will briefly present some points of view regarding open access to academic information sources, definitions of open access and what free source or open source means. Defining the objectives of sustainable development as well as the role of universities in the context of the current world is essential in order to form the correct opinion among the beneficiaries of academic information sources. The objectives of Angeda 2030 for sustainable development and their application to the academic world will be defined and solutions will be proposed for general access to academic information, without costs or risks of intellectual property infringement. We all know that in creating a research content, the main challenge is to document yourself, without the risk of violating intellectual property and its principles. Last but not least, the work will also offer some recommendations regarding the methods of verifying the veracity of the sources as well as the authenticity of the information.